ANALISA LAPORAN KEUANGAN GUNA MENGUKUR KINERJA KEUANGAN PADA PERUSAHAAN SEMEN DI BURSA EFEK INDONESIA (PERIODE 2017-2018) - Meliani, Silvi; MARETA, FITRI; JASUNI, ANA; Paulina, Elin (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2020)
The financial performance of cement companies on the Indonesia Stock Exchange is toanalyze the company's financial statements. In order to examine the financial condition of the company or not, and can be known using ratio analysis. The purpose of this study is to determine the financial performance of Wijaya Karya Beton, Waskita Beton Precast and Semen Baturaja. The liquidity ratio of Waskita Beton Precast and Semen Baturaja companies has increased, making the company categorized as in a capable state, inversely proportional to Wijaya Karya Beton which has decreased making it not in a capable state. The activity ratio shows the level each year makes the company Waskita Beton Precast and Semen Baturaja said to be in a capable condition, but Wijaya Karya Beton which has decreased makes it not in a capable state. The solvency ratio shows that the company's capital, Waskita Beton Precast, bears little debt to creditors, making the company said to be in a state of incompetence, in contrast to Wijaya Karya Beton and Semen Baturaja are in a capable position. The profitability ratio shows an increase from year to year. It can be said that Karya Beton, Waskita Beton Precast and Semen Baturaja are in a capable position even though Waskita Beton Precast has decreased slightly.